Assessment of Preoperative and Postoperative Changes in Corneal Astigmatism after Pterygium Excision by Di?erent Techniques - Madhavi Chevuturu (Asian Journal of Medical Research, 2020)
Background: Pterygium causes visual problems due to induced corneal astigmatism or direct encroachment onto the visual axis. The present study was conducted to compare preoperative and postoperative changes in corneal astigmatism after pterygium excision by different techniques. Subjects and Methods: The present study was conducted from May 2018 to August 20018 on 69 patients of age range 20-55 years of primary Pterygium. Patients were divided into three groups of 23 each. Group I was treated with bare sclera (BS) technique, Group II with conjunctival autograft (CAG) technique and Group III with amniotic membrane graft (AMG) technique. All the patients were preoperatively assessed for visual acuity, anterior and posterior segments, autorefraction, and autokeratometry. After surgery, the patients were recalled on day 5, 1 month, and 3 months for the analysis. Results: Uncorrected visual acuity (UCVA) preoperatively was 0.57, on the 5th day was 0.45 after 1 month was and after 3 months was 35. The mean preoperative astigmatism value in group I was 3.45, in group II was 3.52 and in group III was 3.49. Postoperative astigmatism value in group I was 1.60, in group II was 0.92 and in group III was 0.81. The difference was significant (P< 0.05). Conclusion: Authors found that amniotic membrane graft and a conjunctival autograft is better surgical techniques than bare sclera in reducing astigmatism.